A review of advances in resistance spot welding of automotive sheet steels: emerging methods to improve joint mechanical performance - Soomro, I.A. (Springer Science and Business Media Deutschland GmbH, 2022)
The use of resistance spot welding (RSW) in the automotive industry is by far the most preferred and widely used joining technique for sheet metal parts and is likely to continue for the foreseeable future. Advanced high strength steels (AHSSs) are most commonly used in automotive structural components due to their attractive strength-ductility combinations. However, several challenges are faced during RSW including (1) complex phase transformations such as hardening of nugget due to brittle martensitic structure and softening in the heat affected zone due to martensite tempering present in base metal, cast like solidification structure of nugget (2) elemental segregation leading to grain boundary embrittlement, (3) solidification defects such as porosity and void formation in nugget, and (4) liquid metal embrittlement cracking. All of above factors contributes in degradation of joint mechanical properties. In recent years, interlayer assisted RSW, magnetically assisted RSW, and pulsed-RSW have emerged as potential methods to improve the joint mechanical performance. This review paper seeks to summarize the recent technological advances of three modified RSW processes. A comprehensive analysis of the effect of welding process parameters on metallurgical features of the weld joint, mechanical performance, and failure behaviour under different loading conditions, i.e. cross tension, tensile shear, and cyclic (i.e. fatigue), is presented. In addition, the process feasibility to various AHSS grades is also discussed. Finally, current challenges and new opportunities arising from three modified RSW processes are discussed to provide a basis for future research. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag London Ltd., part of Springer Nature.